2019
DOI: 10.35842/jkry.v6i1.261
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Pengetahuan Lansia Mengenai Osteoporosis Melalui Pemberian Pendidikan Kesehatan Dengan Media Audio Visul Di Desa Karangbendo Bantul Yogyakarta

Abstract: Kejadian osteoporosis pada lansia dapat dicegah melalui perilaku hidup sehat. Perilaku hidup sehat didukung oleh pengetahuan. Salah satu upaya untuk meningkatkan pengetahuan lansia adalah melalui penyuluhan kesehatan audio-visual. Kelebihan pendidikan kesehatan audio visual adalah membuat cara  berkomunikasi menjadi efektif, terjangkau, dan materi menarik perhatian serta mudah untuk dipahami. Hal ini akan lebih memudahkan pemberian informasi kepeda lansia mengingat lansia mengalami penurun pada kognitif, pengl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Human behavior is all activities or human activities, both those that are directly observed and those that cannot be observed by outsiders (Notoadmojo, 2013). Health education is one way to increase public knowledge about the dangers of smoking Good knowledge about the dangers of smoking can help adolescents to help themselves in overcoming their health problems and can contribute their energy and abilities for the benefit of their families and communities (Asmarani, 2019). The results of Ikhsan's research (2013) showed that there was a change in the number of cigarettes after being given health education.…”
Section: Resultsmentioning
confidence: 99%
“…Human behavior is all activities or human activities, both those that are directly observed and those that cannot be observed by outsiders (Notoadmojo, 2013). Health education is one way to increase public knowledge about the dangers of smoking Good knowledge about the dangers of smoking can help adolescents to help themselves in overcoming their health problems and can contribute their energy and abilities for the benefit of their families and communities (Asmarani, 2019). The results of Ikhsan's research (2013) showed that there was a change in the number of cigarettes after being given health education.…”
Section: Resultsmentioning
confidence: 99%
“…Asmari, 2019 yang menggambarkan dampak lansia setelah diberikan penyuluhan oleh menemukan hasil rerata pengetahuan sebelum diberikan pendidikan kesehatan sebesar 65.60 dan sesudah diberikan pendidikan menjadi 74.17 dengan nilai signifikasi 0.001 (p<0.05). atau dapat disimpulkan ada peningkatan pengetahuan lansia mengenai osteoporosis melalui pemberian pendidikan kesehatan dengan media audio visul di desa karangbendo bantul Yogyakarta (Asmarani, 2019).…”
Section: Pendahuluanunclassified
“…The elderly are interested in taking part in counseling using video media because apart from listening, they can also see the pictures/illustrations that are shown. These conditions affect the psychomotor of the elderly and make information conveyed are easier to understand, remember, and ultimately can change the attitudes and behavior of the elderly (Asmarani, 2019).…”
Section: Effect Of Video Media On Changes In Elderly Attitudes About ...mentioning
confidence: 99%